Stigmatization and Discrimination Experiences of Persons with Mental Illness: Insights from a Qualitative Study in Southern Ghana - Mavis Dako-Gyeke; Emmanuel Sowah Asumang (Social Work and Society)
Although globally persons with mental illness often experience stigmatization and discrimination, not many studies have focused on their plight, especially in Ghana. This study, which goes beyond current research, examined stigmatization and discrimination experiences of persons with mental illness in Accra. The study sought to explore the nature of stigma and discrimination experienced by persons with mental illness. A purposive sampling method was used to recruit twenty participants and in-depth interviews were conducted to gather data for the study. The findings revealed that persons with mental illness were stigmatized and discriminated against in their interactions with their family members, friends, neighbors, employers and colleagues at work. Based on the findings, implications for mental health practice are discussed.